Uczniowie źli i bardzo źli = Poor and very poor students - Zahorska, Marta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The educational reform of 1999 changed the structure of the Polish educational system. A new kind of school was created - lower secondary school ("gimnazjum"). One of the objectives of this change was to equalize the education levels (or rather to reduce the differences) between urban and rural schools. Unfortunately, the results of external exams have shown a systematic deepening of these differences. Rural schools have increasingly poor, and urban schools - increasingly good results.
Keywords: oświata - Polska - po 1945 r.; szkolnictwo polskie; szkolnictwo ponadpodstawowe; reformy; gimnazjum; młodzież wiejska